Hubungan Antara Kualitas Tidur Dengan Memori Jangka Pendek Pada Anak Usia 5-6 Tahun Di TK Pembina Garoga - Rawaty O F Panggabean; Artha Mahindra Diputera (Jurnal Pena Pendidikan Dasar, 2026)
In early childhood, good sleep quality plays a crucial role in brain development and readiness for learning. This study aims to examine the relationship between sleep quality and short-term memory in 5-6 year old children at Pembina Garoga Kindergarten in North Tapanuli, Indonesia. The study design was quantitative and correlational. The sample consisted of 24 children selected via random sampling from a population of 30 children. Sleep quality was measured using the parent-completed adapted Pittsburgh Sleep Quality Index (PSQI), which covers seven dimensions: latency, duration, continuity, subjective quality, refreshment upon waking, efficiency, and behavioral disturbances. Short-term memory was measured through a performance test consisting of six tasks: repeating numbers, repeating words, following three-step instructions, recalling visual objects (picture cards), repeating sentences, and retelling a story. Data analysis utilized descriptive statistics and Pearson’s correlation using Jamovi. Results indicated that 79.2% of children had very good sleep quality and 20.8% had good sleep quality, while 62.5% had good short-term memory, 33.3% had adequate short-term memory, and 4.2% had very good short-term memory. The Pearson correlation test revealed a significant positive relationship between sleep quality and short-term memory (r=0.470, p=0.020), with moderate strength. These findings confirm that the better a child’s sleep quality, the higher their short-term memory capacity. The study concludes that sufficient and high-quality sleep enhances a child’s ability to temporarily store and retrieve information, which is essential for classroom learning. Parents and teachers should prioritize healthy sleep habits as part of a strategy for early childhood cognitive development.